Ganoderma lucidum: Current advancements of characteristic components and experimental progress in anti-liver fibrosis - Peng, Haoyuan; Zhong, Lei; Cheng, Lin; Chen, Lu; Tong, Rongsheng; Shi, Jianyou; Bai, Lan (Frontiers in Pharmacology, 2023)
Ganoderma lucidum (G. lucidum, Lingzhi) is a well-known herbal medicine with a variety of pharmacological effects. Studies have found that Ganoderma lucidum has pharmacological effects such as antioxidant, antitumor, anti-aging, anti-liver fibrosis and immunomodulation. The main active components of Ganoderma lucidum include triterpenoids, polysaccharides, sterols, peptides and other bioactive components. Among them, the triterpenoids and polysaccharide components of Ganoderma lucidum have a wide range of anti-liver fibrotic effects. Currently, there have been more reviews and studies on the antioxidant, antitumor and anti-aging properties of Ganoderma lucidum. Based on the current trend of increasing number of liver fibrosis patients in the world, we summarized the role of Ganoderma lucidum extract in anti-liver fibrosis and the effect of Ganoderma lucidum extract on liver fibrosis induced by different pathogenesis, which were discussed and analyzed. Research and development ideas and references are provided for the subsequent application of Ganoderma lucidum extracts in anti-liver fibrosis treatment.